Straits, Passages and Chokepoints: A Maritime Geostrategy of Petroleum Distribution - Rodrigue, Jean-Paul (Cahiers de géographie du Québec)

(untitled) (Département de géographie, 2004)
AbstractThe transportation of petroleum represents one of the most strategically important circulations of resources in the global economy. Its role cannot be overstated. Yet, petroleum has become a “strategically invisible” commodity as its flow has been continuous with limited, but eye-opening, disruptions such as the First Energy Crisis is 1973. Petroleum supplies are virtually taken for granted. Since approximately two-thirds of the world’s petroleum production is shipped by sea, there are inherent distribution constraints, which require navigating through straits and passages; chokepoints of maritime circulation. This paper presents an overview of the geography of oil supply and demand, and the strategic issues that are linked to its maritime circulation. Chokepoints are perceived as resources, the value of which varies according to degree of use. As the era of petroleum domination draws to a close, the importance and vulnerability of strategic passages will increase. Their ability to handle additional traffic appears to be limited, implying that future energy crises or oil shortages are more likely to be attributable to the challenges of distribution.